Introduksi Rumput Laut Turbinaria murayana sebagai Bahan Pakan Unggas pada Kelompok Ternak Sungai Nipah Kabupaten Pesisir Selatan - Sepri Reski; Yose Rizal; Maria Endo Mahata (Warta Pengabdian Andalas, 2022)
This program was carried out on the Nipah River Coast farmers group, Pesisir Selatan Regency, West Sumatra Province. This activity aims to overcome the problem of the availability of feed ingredients that are not continuous, the price is relatively high, and their use is still competitive with human needs such as corn and fish meal. In addition, this activity aims to introduce the method of processing brown seaweed of the Turbinaria murayana species, which grows a lot around the Nipah River Coast, Pesisir Selatan Regency, which can be utilized and processed as poultry feed ingredients. This community service activity is carried out using counselling and training methods. The extension activities included introducing the taking and processing of T. murayana brown seaweed for poultry feed ingredients. Training consisted of pilot processes and practical exercises in processing T. murayana seaweed as poultry feed ingredients. Participants in this service activity consisted of 20 men and women. The results of this activity can improve the knowledge and skills of farmers regarding seaweed processing in the Sungai Nipah Coastal area, Pesisir Selatan Regency. The conclusion of this community service activity is the increase in farmers' knowledge and skills about the potential use of T. murayana seaweed and its processing as poultry feed ingredients.